Railway-Oriented Spatial Development. A Principal Strategy for Integrated Spatial and Railway Development in Small and Mid-Sized Communities of Swiss Agglomerations. - Soltaniehha, Mahdokht (My University, 2019)
The main hypothesis of this dissertation is that underdeveloped and empty land reserves in the catchment area of the railway stations can potentially contribute as a key drive for more compact forms of development in agglomerations. This is of paramount importance for densification in small and mid-sized communities, where more than 60% of land reserves are available. Thus, considering the potentials for compact development in the catchment area of railway stations, this work addresses coordinated spatial and transportation policy-making as an essential requirement for a principal strategy of “inward development before outward development”, and as preparation for a new strategy of “Railway-Oriented Spatial Development” (ROSD). Implementation of ROSD is confronted with various operational obstacles: fragmented local governance, general obligations of national and regional governments and low planning competence of the small and mid-sized communities, along with others. Identifying the complex planning tasks that ROSD should potentially tackle, this work evaluates the existing planning instruments, and proposes a new collaborative instrument of ‘corridor consilium’, which identifies the transit corridors as functional regions and clarifies the causes of the abovementioned problems. Missing collective understanding of the problem, sectoral planning and diverging interests, lack of planning cooperation beyond administrative borders and planning for functional spaces, to list but some of the aspects, can be the focus of a corridor conference. Therefore, a corridor conference facilitates the decision-making processes towards achieving the minimum strategy of ROSD, especially for small and mid-sized communities

Der Implementierung von "Railway-Oriented Spatial Development“ (ROSD) stehen mehrere operationelle Hindernisse im Weg, u. a. fragmentierte lokale Verwaltungen, generelle Auflagen nationaler und regionaler Regierungen sowie die geringere Planungskompetenz in kleinen und mittelgroßen Gemeinden. Um die komplexen Planungsaufgaben zu identifizieren, welche ROSD potenziell bewältigen muss, evaluiert die Arbeit die bestehenden Planungsinstrumente und schlägt ein „Korridor Konsilium“ als neues Kooperationsinstrument vor. Dieses identifiziert strategisch bedeutsame Transitkorridore als funktionale Regionen und klärt die Ursachen der erkannten Schwierigkeiten. Die Korridor-Konferenz soll beispielsweise fehlendes kollektives Problemverständnis, sektorspezifische Planung und divergierende Interessen, mangelnde planerische Kooperation über Verwaltungsgrenzen hinweg sowie fehlende Planungsmaßnahmen für funktionale Regionen überwinden helfen. Speziell in kleinen und mittleren Gemeinden soll damit ein wichtiger Beitrag geleistet werden, um die Zusammenarbeit an einer für die nächsten Jahrzehnte zentralen und im gemeinsamen Interesse liegenden Aufgabe zu stärken: der vom Gesetzgeber geforderten Siedlungsentwicklung nach innen.
Eisenbahnorientierte Raumentwicklung. Eine Hauptstrategie für die integrierte Raum- und Eisenbahnentwicklung in kleinen und mittleren Gemeinden der Schweizer Agglomerationen.
Keywords: Raumentwicklung; Siedlungsentwicklung; Innenentwicklung; Verkehrsachse; Schienennetz; Eisenbahn; Öffentlicher Verkehr; Planungsinstrument; Planungskooperation; Siedlungsstrukturentwicklung; Regionalwirtschaft; Grenzraum; Governance; Befragung; Verdichtungsraum; Bodenpolitik